Perú: políticas para cerrar la brecha de la balanza de conocimientos - Roca Tavella, Santiago (2011)
In this paper we show the balance of knowledge deficit in Peru compared to the surplus of its trade balance and the necessity to transform the structure and technological coefficients of exports to close this knowledge gap. We analyze major economic policies that could help in closing the gap, especially industrial and technological innovation policies, rethinking intellectual property rights and impelling the forces that propagate the economic system as a whole. “Openness” and the “good management of macroeconomic fundamentals” are necessary but not sufficient conditions to transform the economy, which for better performance need the strategic “will and wit” of adding value and a better balance between external and national interests.